2009 16th IEEE International Conference on Image Processing (ICIP) 2009
DOI: 10.1109/icip.2009.5414069
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast optic disc localization using projection of image features

Abstract: Optic Disc (OD) localization is a fundamental step in developing computer-assisted diagnostics. In this work, an ultrafast method to locate the OD in retinal fundus images is presented. The proposed method is based on transforming the localization problem into two 1D problems by projecting the image features onto two perpendicular directions. Image features such as the directionality of the retinal vessels, the brightness and the size of the OD have been used in the current method. Two publicly available datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Template matching methods consider the gray-level characteristic of the OD to find region of interest (ROI) which contains OD [14]. Mahfouz et al [15] found ROI containing OD, so that it is the brightest region in comparison to other areas in the fundus image. Then, a circular matched filter computed cross-correlation with a pre-computed ROI.…”
Section: Introductionmentioning
confidence: 99%
“…Template matching methods consider the gray-level characteristic of the OD to find region of interest (ROI) which contains OD [14]. Mahfouz et al [15] found ROI containing OD, so that it is the brightest region in comparison to other areas in the fundus image. Then, a circular matched filter computed cross-correlation with a pre-computed ROI.…”
Section: Introductionmentioning
confidence: 99%
“…Template matching methods consider that optic disc is a high bright region in the image relative to other areas. Mahfouz et al [6] found a region of interest (ROI) containing optic disc. Then, it applied a circular matched filter to compute cross-correlation with a pre-computed ROI.…”
Section: Introductionmentioning
confidence: 99%